Spiritual Experiences of Transcendence in Patients With Advanced Cancer. (March 2015) - Renz, M.; Mao, M. Schuett; Omlin, A.; Bueche, D.; Cerny, T.; Strasser, F.
Purpose: Spirituality encompasses a wide range of meanings between holistic wellbeing and mysticism. We explored advanced cancer patients' spiritual experiences of transcendence. Methods: A total of 251 patients with advanced cancer were included and observed (participant observation) over 12 months by a psycho-oncologist/music-therapist. She recorded and documented patients' spontaneously expressed spiritual experiences during hospitalisation. Interpretative Phenomenological Analysis was applied. Results: 135 patients communicated a spiritual experience, as expressed by altered body-awareness, less pain, less anxiety, higher acceptance of illness/death, new spiritual identity. Spiritual experiences were communicated by patients across different religious affiliations/attitudes. We identified types of spiritual experiences. Conclusion: The occurrence of spiritual experiences seems to be frequent and associated with profound, powerful reactions. Our results indicate that experienced-based spiritual care may complement current needs-based approaches.